Análise eletroencefalográfica do controle postural durante estimulação visual em ambiente de realidade virtual estereoscópica - Gandra, Viviany Dias. (2019)
Spatial orientation in postural control is based on the interpretation of sensory information from somatosensory, vestibular and visual systems. Dynamic visual stimulation can be performed in a virtual reality environment, capable of provoking postural changes during balance maintenance, particularly when using stereoscopy, when an individual’s presence (immersion) sensation is expected to increase in the virtual environment. The aim of the present study was to investigate the effect of dynamic visual stimulation on cortical processing of orthostatic and seated postural control in order to estimate M-VEP. Twenty-five healthy volunteers with an age range of 28.24 ± 7.06 years participated in this study. EEG signals were collected while a virtual scenario was shifted antero-posteriorly in a pseudo-random fashion, approaching or moving away from the observer. The P3 component of the M-VEP during spacing presented greater amplitude than the one elicited by the approach, with both standing and sitting individuals. The responses to standing position stimuli presented higher latency variation for approximation, while the P3 peak amplitude variability was higher for the distance from the scenario. With the sitting individuals, both latency and amplitude presented greater variation of P3 for approximation. Comparing the responses of the stimuli in the orthostatic position and in the sitting position, no significant difference was obtained, although it is possible to observe that sitting individuals end up having less immersion because of the instability theory.